Clinical Application of Computed Tomography on Prostate Volume Estima¬tion in Patients with Lower Urinary Tract Symptoms - Kang, Tae Wook; Song, Jae Mann; Kim, Kwang Jin; Byun, Hyun Keun; Kim, Young Joo; Chung, Hyun Chul; Chae, Yun Byung; Kim, Hong Wook; Jung, Jae Hung (Urology Journal, 2014)
Purpose: To compare estimated prostate volume (PV) based on computed tomography (CT) scan and transrectal ultrasonography (TRUS) in patients with lower urinary tract symptoms (LUTS). Materials and Methods: Between January 2010 and October 2012, 107 consecutive patients with LUTS were analyzed, retrospectively. PV measures were performed by the means of ellipsoid formula (PV = π/6 [width (cm) thickness (cm) length (cm)]) from TRUS (PVTRUS) and CT (PVCT ellipsoid). In addition, PV was calculated as the sum of the area of each slice and the CT slice interval using commercial software program (PVCT 3D reconstruction). Results: Mean PVCT ellipsoid was 40.63 ± 31.06 cm3 (range, 8.34-217.46). Mean PVTRUS and PVCT 3D reconstruction were 39.20 ± 33.04 (range, 4.00-223.81) and 45.30 ± 32.98 (range, 8.90-248.30), respectively. PVCT ellipsoid was highly correlated with PVTRUS and PVCT 3D reconstruction (r = 0.935, P < .001; r = .970, P < .001, respectively). Moreover, there was very strong agreement for PV measurements with all three methods (intraclass correlation coefficient = 0.934, P < .001). Conclusion: PVCT ellipsoid is adequate method for quick volume assessment with reasonable accuracy. Therefore, we can easily predict PV by CT scan using ellipsoid formula without performing additional TRUS in patients with LUTS.